Science in the Whirlwind of Religion and Power - Amhar, Fahmi; Puri, Anas (Islamic Research, 2025)
This paper examines the interactions among science, religion, and power across historical and social contexts. Science is defined as a systematic effort to build knowledge through testable explanations and predictions, while religion is a system that connects humans with supernatural and transcendental elements. Power, in this context, is understood as a social production that shapes actors' capacities, actions, and beliefs. The paper outlines a crisis of thinking and literacy among scientists, religious scholars, and politicians, who often fail to understand or disregard the relevance of other fields. Various types of relationships between power and both science and religion are described, including power that protects, suppresses, restricts, utilizes, or mediates between the two domains. Additionally, the paper discusses how religion and science can influence or even conflict with each other. Historical examples of the complex interactions between science, religion, and power are provided, showing that harmony among them can lead to progress, while imbalance can result in regression. In conclusion, Muslims need to understand and appropriately position science, religion, and power to avoid secular extremism and ensure balanced development in society.